2009
DOI: 10.1111/j.1365-2672.2008.04056.x
|View full text |Cite
|
Sign up to set email alerts
|

Destruction ofBacillus licheniformisspores by microwave irradiation

Abstract: Aims:  To investigate the sporicidal mechanisms of microwave irradiation on Bacillus licheniformis spores. Methods and Results:  We measured spore viability and the release of DNA and proteins, and performed transmission electron microscopy (TEM). A microwave oven (0·5 kW) was modified to output power at 2·0 kW, which allowed a shorter sterilization cycle. A 2·0 kW microwave treatment at the boiling temperature for 1 min did not kill all spores, but killed most spores. The spore inactivation rate was faster th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…S1). MW radiation can increase cell membrane permeability by rupturing the spore coat and inner membrane, which results in the increased leakage of electrolytes, Ca 2+ , protein and DNA (Fang et al, 2011;Kim et al, 2009). Therefore, the total ARB concentrations of pretreated sludge reduced with the reduction of the total heterotrophic bacteria (HPC) (Fig.…”
Section: Distribution and Fate Of Arb During The Combined Mw Pretreatmentioning
confidence: 99%
“…S1). MW radiation can increase cell membrane permeability by rupturing the spore coat and inner membrane, which results in the increased leakage of electrolytes, Ca 2+ , protein and DNA (Fang et al, 2011;Kim et al, 2009). Therefore, the total ARB concentrations of pretreated sludge reduced with the reduction of the total heterotrophic bacteria (HPC) (Fig.…”
Section: Distribution and Fate Of Arb During The Combined Mw Pretreatmentioning
confidence: 99%
“…In contrast, the Chelex 100-Microwave method is efficient with both types of bacteria. This may be because cellular lysis in this method is caused by the rotation and friction of cell molecules when in the microwave oven (Ling et al 1991;Kim et al 2009), and not by enzymatic collision alone (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…In the suspension of Bacillus licheniformis spores subjected to microwaves with the capacity of 2 kW, numerous proteins and DNA were noted, which got outside through destroyed spore coats. the activity of the protein cotA located in the spore capsule, which did not change its properties during classic boiling, was completely inhibited [21].…”
Section: Discussionmentioning
confidence: 97%